2006
DOI: 10.1002/jctb.1414
|View full text |Cite
|
Sign up to set email alerts
|

Extraction equilibria and separation of phenylalanine and aspartic acid from water with di(2‐ethylhexyl)phosphoric acid

Abstract: The distribution equilibria of single and binary L-phenylalanine and L-aspartic acid between water and a kerosene solution of di(2-ethylhexyl)phosphoric acid (D2EHPA) were studied. It was shown that the distribution ratios of phenylalanine generally increased with increasing aqueous pH (2-5) in the D2EHPA concentration range 0.1-0.5 mol dm −3 , but those of aspartic acid decreased with increasing solution pH. Different reaction stoichiometries were proposed for the extraction of phenylalanine and aspartic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This indicates that a large amount of the complex will be accumulated in the organic phase. Such a behavior can be supported from our previous studies on batch liquid-liquid extraction equilibrium [20].…”
Section: Effects Of Process Variablesmentioning
confidence: 54%
See 1 more Smart Citation
“…This indicates that a large amount of the complex will be accumulated in the organic phase. Such a behavior can be supported from our previous studies on batch liquid-liquid extraction equilibrium [20].…”
Section: Effects Of Process Variablesmentioning
confidence: 54%
“…It is found that n equals 0.5 and the extraction equilibrium constant K ex , defined in Eq. (5), is 23.7 (mol/m 3 ) 1/2 at 25 • C [20].…”
Section: Chemistry Of Liquid-liquid Extractionmentioning
confidence: 98%
“…It is also used in complexation reactions for several organics such as amino acids, polyamines and cationic dyes [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the solubility in nonpolar solvents is very low. Therefore, LLE of amino acids is generally achieved by adding the organic phase extractants such as phosphoric acid derivatives, quaternary aliphatic amines or crown ethers, etc. mainly including the method of ion‐exchange reaction extraction, liquid membrane extraction or reversed micelle extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic interaction was involved in many amino acids extraction either using acidic extractant (e.g. di(2‐ethylhexyl) phosphoric acid (D2EHPA)) or basic extractant (e.g. trioctylamine (TOA)) or using reversed micelles formed by anionic surfactant (e.g.…”
Section: Introductionmentioning
confidence: 99%